(untitled) (Bangladesh Heart Journal, 2019)
Background: Preoperative risk assessment before cardiac surgery to predict mortality become literally important and practicing worldwide, whereas EuroSCORE II is most updated and popular. So we examined the hypothesis that Performance of EuroSCORE II in predicting early mortality after Mitral, Aortic or mitral & aortic valve surgery patients in National Heart Foundation Hospital and Research Institute. Objectives: To compare Euro SCORE II predicted early mortality and observed early mortality in a sample of patients of National Heart Foundation Hospital who underwent for Mitral, Aortic or Mitral & Aortic valve surgery. Methods: An observational prospective study was done in Department of cardiac surgery, National Heart Foundation Hospital and Research Institute who underwent for Mitral, Aortic or Mitral & Aortic valve surgery in the period of July 2016 to March 2018. Sample size was 356 and all inclusion criteria full filled. Patients were divided into 3 group (low, medium & high) depending on the score. Model discrimination and calibration were assessed additive and logistic EuroSCORE and EuroSCORE II. Results: The in hospital mortality of this series was 2.8% (10 out of 356) and the predicted mortality was 2.73% (95% CI 1.02-4.38) by the EuroSCORE II, 2.15% (95% CI 0.68- 3.72) by the additive method and 2.25% (95% CI 0.74-3.86) by the logistic EuroSCORE. The model’s discriminatory power also good and useful as indicated by an area under ROC curve of 0.779 in EuroSCORE II model, 0.675 in additive method and 0.696 in logistic method that means EuroSCORE II method can predict the outcome with 77% accuracy, additive method with 67% accuracy and the logistic method does that with 69% accuracy. Conclusion: EuroSCORE II was validated and performed well on National Heart Foundation patients and could be recommended as a simple risk stratification system to estimate the probability of early mortality in patients scheduled for valve surgery in Bangladesh. Bangladesh Heart Journal 2019; 34(1) : 11-24